ANALISIS ASPEK BAHASA DAN NILAI SOSIAL BUDAYA DALAM DRAMA OIDIPUS - Sujito Sujito (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2014)
This study describes intrinsic analysis of Drama text written by Sophocles, focusing on general and social aspects of analysis. Content analysis was used in this study to examine the text of the drama. The study concluded that the Legend of Thebes represented in Oidious the King inherently reflected valuable linguistic and social values.  Written by a wellknown author, Sophocles, Oidious the King presented setting sensitive aspects of natural characters of human beings. Social values that involved democratic, religious, loyality, living harmoniously in the community were well described in this drama.